Teacher qualifications in the implementation of the Kurikulum Merdeka and ISMUBA - Tarso Tarso; Deny Hadi Siswanto; Aldo Setiawan (Curricula: Journal of Curriculum Development, 2025)
Developing flexible and innovative curricula is essential to meet the demands of 21st-century education. This study examines the curriculum's planning, implementation, and evaluation at SMA Muhammadiyah Mlati, focusing on teacher qualifications and the relevance of learning materials to contemporary knowledge advancements. A qualitative descriptive method with an exploratory case study design was employed, involving principals, vice-principals, and teachers as research subjects. Data were gathered through interviews, documentation, and observations. The findings indicate that the school has implemented the Merdeka Curriculum, which is integrated with the ISMUBA curriculum. This approach is tailored to students' needs, environmental potential, and the Ministry of Education and Muhammadiyah guidelines. The curriculum has improved educational quality significantly. Flagship programs such as Life Skills and Pondok Tahfidz also foster character development and competitiveness, leading to remarkable academic and non-academic achievements.   Abstrak Pengembangan kurikulum yang fleksibel dan inovatif telah menjadi kebutuhan penting bagi siswa di era modern. SMA Muhammadiyah Mlati menciptakan kurikulum yang sesuai dengan kebutuhan siswa abad ke-21. Penelitian ini bertujuan untuk menganalisis proses perencanaan, pelaksanaan, dan evaluasi kurikulum, termasuk kualifikasi guru dan relevansi pembelajaran terkait dengan kemajuan ilmu pengetahuan. Penelitian menggunakan metode deskriptif kualitatif dengan desain studi kasus eksploratif, yang melibatkan kepala sekolah, wakil kepala sekolah, dan guru sebagai subjek penelitian. Data dikumpulkan melalui wawancara, dokumentasi, dan observasi. Hasil penelitian menunjukkan bahwa sekolah ini telah mengembangkan Kurikulum Merdeka yang terintegrasi dengan kurikulum ISMUBA. Kurikulum ini dirancang berdasarkan kebutuhan siswa, potensi lingkungan, dan arahan dari Kementerian Pendidikan serta Muhammadiyah. Pengembangan kurikulum ini telah meningkatkan kualitas pendidikan. Sekolah juga meluncurkan program unggulan seperti Life Skills dan Pondok Tahfidz untuk mendukung pengembangan karakter dan meningkatkan daya saing, yang menghasilkan pencapaian akademik dan non-akademik yang signifikan. Kata Kunci: kualifikasi guru; kurikulum ISMUBA; Kurikulum Merdeka